Word of the Lourd satire on the Philippine television perceptions of Metro Manila youth on Word on the Lourd - Cruz, Carl Benedict Tizon (2013)
Mass media is a very powerful communication tool. It has the power to portray and shape the perception of its audience. One form of mass media is television. It is used by people for information and entertainement it offers through its programs and shows. However, recent studies have shown that the youth of today found traditional news programs to be 'repetitive' and 'lacking entertainment value'. Word of the Lourd is a TV segment that pans current social and political issues in the Philippines society using satire. According to some studies, the use of humor leads the audience to think more critically, thus, encourage them to be engaged to the show. In this light, the researcher tried to determine how Metro Manila youth regarded Word of the Lourd. The study explored on the knowledge, exposure and perceptions of the respondents towards the show. Having a descriptive-quantitative method for the study, 22-item questionnaire was developed and distributed to 200 Metro Manila youth to determine their knowledge, exposure and perceptions on WOTL. For the data analysis, the researcher applied audience analysis by interpreting answers using frequency count and percentage equivalence. Concepts from the Uses and Gratification Theory and Cultivation Theory also guided the researcher in analyzing the data. The findings showed that Metro Mnila youth had a positive perceptions on Word of the Lourd. The results also revealed that exposure and knowledge about the show would not necessarily yield positive effects on the perceptions of the audience. Furthermore, the use of satire of Word of the Lourd in panning social and political issues in the Philippine society, was found by the respondents as appealing. These positive findings may pave the way for applying satire in TV news programs to make them more entertaining and appealing. If proven effective, it may revolutionize TV's methods to get an idea across, especially to the younger audience."